2021
DOI: 10.3390/nu13114084
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nutritional Interventions on Cardiovascular Disease Health Outcomes in Aboriginal and Torres Strait Islander Australians: A Scoping Review

Abstract: Nutrition interventions can support Aboriginal and Torres Strait Islander peoples to reduce their risk of cardiovascular disease (CVD). This review examines nutritional interventions aiming to improve CVD outcomes and appraises peer-reviewed interventions using an Aboriginal and Torres Strait Islander Quality Appraisal Tool. Five electronic databases and grey literature were searched, applying no time limit. Two reviewers completed the screening, data extraction and quality assessment independently. The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In their scoping review of the effects of nutritional interventions on cardiovascular health outcomes in First Australian communities, Porykali and colleagues found the most successful projects were those of the longest duration [20]. The short-term nature of the funding was an issue in our project.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In their scoping review of the effects of nutritional interventions on cardiovascular health outcomes in First Australian communities, Porykali and colleagues found the most successful projects were those of the longest duration [20]. The short-term nature of the funding was an issue in our project.…”
Section: Discussionmentioning
confidence: 92%
“…A systematic review of 26 nutrition-related interventions in First Australians found that only half of the studies achieved moderate or strong community engagement [19]. A scoping review of 21 nutrition interventions for cardiovascular disease with First Australians found that while most of the interventions achieved community engagement and capacity strengthening, few reported taking a strengths-based approach or adopting Indigenous research paradigms and governance [20]. An approach that deeply and authentically involves the community concerned in the research process would clearly be advantageous.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of funding and resource allocation should be acknowledged as a barrier to ongoing program implementation [ 32 ]. This is a common theme across all First Nations research, and it is well known that community-based programs in Australia experience barriers, including adequate funding for end-to-end holistic programs that are evaluated and sustainable [ 53 ], and the lesson is to provide for long-term funding.…”
Section: Discussionmentioning
confidence: 99%
“…Papers that received a ‘yes’ or ‘partially’ for six to nine questions were considered to be of moderate quality and papers that received a ‘yes’ or ‘partially’ to five or fewer questions were considered to be of low quality and less culturally appropriate [ 24 ]. To assess how well each individual question performed across all of the peer-reviewed papers, three marks were assigned for a ‘yes’, two for a ‘partially’, one for an ‘unclear’, and zero for a ‘no’ [ 25 ].…”
Section: Methodsmentioning
confidence: 99%